OKR IN THE ACCOUNTING SYSTEM: A MODERN TOOL FOR IMPROVING MANAGEMENT EFFICIENCY (Development Service Industry Management, 2024)
The article is devoted to the comprehensive analysis of the integration of the OKR (Objectives and Key Results) system into the modern accounting framework. It examines the essence of the OKR methodology, delving into its historical development, core principles, and the conceptual foundation that underpins its effectiveness in organizational management. The article explores its key components, such as setting ambitious yet achievable objectives, defining measurable key results, and ensuring regular monitoring to track progress. Special attention is given to the specific features of OKR’s application within accounting systems, highlighting how it can enhance transparency, streamline reporting processes, and improve overall efficiency in enterprise management.Moreover, the article highlights the numerous advantages of implementing OKR, including the alignment of strategic goals across different levels of the organization, improved internal communication, and fostering a culture of accountability. The system helps bridge the gap between strategic planning and day-to-day operations, ensuring that every department and employee understands how their work contributes to the company's broader mission. Additionally, OKR promotes transparency in accounting processes, enabling stakeholders to track performance metrics in real-time.However, the article also draws attention to the challenges that may arise during the implementation of OKR. These include the need for significant policy adaptation, changes in organizational culture, and comprehensive personnel training to ensure that employees understand and embrace the new system. Resistance to change, lack of clear guidelines, and difficulties in setting appropriate key results are common obstacles.It is separately noted that OKR is not just a management tool but also a powerful mechanism for enhancing the competitiveness of enterprises in dynamic market environments. By fostering agility, adaptability, and continuous improvement, OKR supports companies in responding to external changes more effectively. The potential of OKR to improve decision-making processes, encourage data-driven strategies, and contribute to sustainable development is emphasized, making it an invaluable asset for modern businesses striving for long-term success.
Keywords: OKR (Objectives and Key Results); accounting system; management transparency; strategic goals; enterprise competitiveness; policy adaptation; sustainable development